Charophytes from Silveirinha (?Upper Paleocene - Lowermost Eocene) according to Janine Riveline - Antunes, M. Telles (2010)
Charophytae gyrogonites are common among the washing/sieving residues from the important ?Upper Paleocene or lowermost Eocene site of Silveirinha (lower Mondego, Portugal). The whole Charophyte material has been submitted to Janine Riveline, who recognized but Nitellopsis (Tectochara) dutemplei (Watelet)Grambast & Souliè-Marsche minor Riveline. This form has been found in the lacustrine marls overlying the "Conglomerat de Cernay" that is rich in late Thanetian vertebrates. Taking into account the presence of the above referred form, the age of the concerned sediments may be (not basal) Sparnacian, Peckichara disermas Charophyte zone.